AdFiT v1.7 (Admixture Files Tool): input files creating tool for population genetic admixture estimation software - Géraud Gourjon; Anna Degioanni (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The six most commonly used software programs in the literature for population genetic admixture estimation since 20 years, are ADMIX, ADMIX95, Mistura, Admix 2.0, LEA, and LEADMIX, and each one has its own specific file format and filename extensions. We present a specific tool that can help in the file creation process: AdFiT (Admixture Files Tool) version 1.7, a multi-language software (English, French and Spanish). It allows, from a common file containing data, to instantaneously create input files for these six software programs and two others, Parallel LEA (ParLEA) and Mixtur. The use of several software programs and all the available genetic markers appears to be mandatory to estimate efficiently the admixture rates. This requires the creation of multiple input files, for each software file format and leads to a wide data handling, increasing the risk of keyboarding errors. AdFit can do it quickly, simply (easily) and without errors. AdFiT is freely available online for academic users.